The Effect of Leadership and Emotional Intelligence on Teacher’s Performance - Yusniarti, Yusniarti; arif, m; Junaidi, Junaidi; Iswantir, Iswantir; Ayu, Sovia Mas (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2022)
The performance of teachers from several State Islamic Senior High School (MAN) in Kota Padang Panjang was classified as not optimal yet, that led to lack of performance in finishing the teachers’ task and function in this New Normal era. The aim of this study was to determine the effect of the principal’s leadership and emotional intelligence on the performance of MAN teachers in Kota Padang Panjang during the New Normal era. This research used quantitative method to determine the problems occurred in the field. The population of this study were 173 teachers, with the research samples chosen was 116 people. The sample was chosen by using Cochran technique, namely stratified proportional random sampling. The data were collected by using questionnaires. Then, they were analyzed by SPSS version 17. The results of this study showed that: (1) The positive and significant effect of the principal's leadership on the performance of MAN Kota Padang Panjang teachers: The effect of the principal’s leadership on the performance of MAN Kota Padang Panjang teachers was 0.357 with a coefficient of determination of 0.1274 or (12.74%); (2) The positive and significant effect of emotional intelligence on the performance of MAN Kota Padang Panjang teachers: Performance of MAN Kota Padang Panjang teachers during the New Normal era was determined by intelligence emotional, that was equal to 0.302 with a coefficient of determination of 0.0912 or 09.12%; (3) The positive and significant effect of both principal’s leadership and emotional intelligence on the performance of MAN Kota Padang Panjang teachers  in the New Normal era, and the performance of MAN Kota Padang Panjang teachers in the New Normal era were determined by the principal’s leadership and emotional intelligence altogether by 0.652 with a coefficient of determination of 0.42.51 or 42.51%.